Translator, Touretter: Avant-Garde Translation and the Touretter Sublime - Robinson, Douglas, (Literature and Cultural Studies E-Books Online, Collection 2024., 2024)
Experimental translation has been surging in popularity recently-with avant-garde translation at the combative forefront. But how to do it? How to read it? Translator, Touretter plays on the Italian dictum traduttore, traditore -"translator, traitor"-to mobilize the affective intensity of Tourettic tics as a practical guide to making and reading avant-garde translations. It smashes the theoretical literature on the sublime from Longinus to Kant into Motherless Brooklyn , both the 1999 novel by Jonathan Lethem and its 2019 screen adaptation by Edward Norton, in order to generate out of their collision a series of models-visual, aural/oral, and kinesthetic-for avant-garde literary translation.